Personal Dosimetry in Continuous Photon Radiation Fields with the Dosepix Detector - Haag, Dennis; Schmidt, Sebastian; Hufschmidt, Patrick; Eberle, Franziska; Michel, Thilo; Anton, Gisela; Hupe, Oliver; Roth, Jurgen; Fuhg, Christian; Zutz, Hayo; Behrens, Rolf; Campbell, Michael; et al. (IEEE Transactions on Nuclear Science, 2021)
First measurements characterizing dosimetric properties of a dosimetry system designed for the purpose of active personal dosimetry for photons with mean energies from 12.4 keV to 1250 keV according to PTB requirements are presented. The system consists of three Dosepix detectors, which is a hybrid, pixelated, photon-counting X-ray detector. The energy and angular dependence of the normalized response and the coefficients of variation of the personal dose equivalents Hp(10) and Hp(0.07) are determined on an ISO water slab phantom in continuous reference photon radiation fields according to ISO 4037-1 and ISO 4037-3. The energy response is presented for the narrow spectra N-15 to N-300 and the radiation qualities S-Cs and S-Co for angles of incidence of 0 °, 30 ° and ±60 °. The highest deviation of the response from the reference response is found at N-60, -60 ° with 1.179±0.007 (standard deviation) for Hp(10). The energy range of use for Hp(10) is expected to extend from 12.4 keV to 1250 keV. For the personal dose equivalent Hp(0.07) the normalized response at ±60 ° is below the lower limit for N-15, N-20 and N-25. It results in an energy range of use from 24.6 keV to 1250 keV. The coefficient of variation increases with increasing photon energy and stays below 1% for all measurements.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Active personal dosimetry; Aluminum; Detectors; Dosimetry; dosimetry with ionizing radiation; hybrid pixel detector; ISO Standards; Phantoms; Photonics; Uncertainty